2023
DOI: 10.1021/acs.langmuir.3c00765
|View full text |Cite
|
Sign up to set email alerts
|

Suberic Acid-Based Supramolecular Metallogels of Ni(II), Zn(II), and Cd(II) for Anti-Pathogenic Activity and Semiconducting Diode Fabrication

Abstract: The importance of three synthesized metallogels of suberic acid distinctly with nickel, zinc, and cadmium acetate salts has been uncovered. For the creation of these soft materials, N,N′-dimethyl formamide was utilized as a source of the trapped solvent. The synthesized metallogels display intriguing viscoelasticity, and the interpretation of experimental parameters obtained from rheological results advocates the gel behavior. Microstructural analysis combined with energy-dispersive X-ray confirms the occurren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 62 publications
0
17
0
Order By: Relevance
“…In general, metal ions exhibit diverse antimicrobial activities, and these properties have been recognized throughout the history of medicine and healthcare. In this study, the metallogels showed antimicrobial activity against both Gram-positive and Gram-negative bacteria . However, the effectiveness of antimicrobial activity varies between metallogels. , In the present work, it was found that Ni­(II)-metallogel showed slight antimicrobial efficiency compared to Co­(II)-metallogel and Zn­(II)-metallogel of azelaic acid used as the low molecular weight organic gelator. These differences in the antimicrobial activity of the metallogels could be due to the differences in the bioavailability of the metal ions during gel-formation.…”
Section: Resultsmentioning
confidence: 53%
See 1 more Smart Citation
“…In general, metal ions exhibit diverse antimicrobial activities, and these properties have been recognized throughout the history of medicine and healthcare. In this study, the metallogels showed antimicrobial activity against both Gram-positive and Gram-negative bacteria . However, the effectiveness of antimicrobial activity varies between metallogels. , In the present work, it was found that Ni­(II)-metallogel showed slight antimicrobial efficiency compared to Co­(II)-metallogel and Zn­(II)-metallogel of azelaic acid used as the low molecular weight organic gelator. These differences in the antimicrobial activity of the metallogels could be due to the differences in the bioavailability of the metal ions during gel-formation.…”
Section: Resultsmentioning
confidence: 53%
“…However, the achievement of self-healing metallogel is still challenging due to the complicated intrinsic mechanisms leading to a metallogelation process, and most of the potential metallogels are discovered by serendipity. , Metal–ligand coordination interaction existing between the gelator molecule and metal ions is one of the premiere driving forces leading to metallogelation . The presence of some typical functional groups within a molecule including carboxylic groups, , hydroxyl groups, phosphate groups, and compounds with oxygen, nitrogen, and sulfur donor sites is an essentially crucial feature of a low molecular weight gelator (LMWG). Additionally, some of the gels based on LMWG exhibit marvelous phase-selective properties that can selectively trap organic solvents from aqueous–organic solvent mixtures . Such gels can be of practical utility in oil spill remedy, phase partition, water treatment, , and in the catalytic reactions of organic compounds …”
Section: Introductionmentioning
confidence: 99%
“…Scientists are very much fascinated about LMOGs not solely for the purpose of academic level but also because of their enormous implementations ranging from the academic to industrial domains, such as chemical sensing, catalytic reaction, organic electronics, , cosmetic industry, conservation of arts, and water purification, and for biological utilities like drug transportation, cellular supports, tissue engineering application, and so on . Apart from these applications, we observe some extra functional properties like redox activity, conductivity, , optical properties, magnetic features, nano science and nano electronics, and proton conductivity, , which are exhibited by the metallogels.…”
Section: Introductionmentioning
confidence: 97%
“…The three-dimensional soft scaffold of supramolecular metallogel is constructed through various types of noncovalent interactions such as van der Waals interactions, hydrogen-bonding, electrostatic interactions, π–π stacking, etc., where the solvent molecules are immobilized. Low-molecular-weight gelators (LMWGs), having molecular mass less than 3000, are very crucial to forming supramolecular gel materials. The incorporation of different functional groups in gelator molecules such as hydroxyl, , carboxylic, phosphate, along with nitrogen, oxygen, and sulfur containing compounds leads to diverse properties of metallogels. It offers potent functionality in different fields of biochemistry, catalysis, antipathogenic activity, medical diagnostics, drug delivery, cell culturing, chemo sensors, tissue engineering, biomineralization, electrochemical devices, nonlinear optics, , lithography, pollutant removal, etc.…”
Section: Introductionmentioning
confidence: 99%